2021
DOI: 10.3390/ijms221910553
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Taken up by Astrocytes

Abstract: Extracellular vesicles (EVs) are composed of lipid bilayer membranes and contain various molecules, such as mRNA and microRNA (miRNA), that regulate the functions of the recipient cell. Recent studies have reported the importance of EV-mediated intercellular communication in the brain. The brain contains several types of cells, including neurons and glial cells. Among them, astrocytes are the most abundant glial cells in the mammalian brain and play a wide range of roles, from structural maintenance of the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…The absorption by astrocytes of exosomes derived from neurons, monocytes, and glial cells, as well as stem cells, has been investigated in some depth [ 62 ]. In the present study, we observed that MuVs were moderately absorbed by astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption by astrocytes of exosomes derived from neurons, monocytes, and glial cells, as well as stem cells, has been investigated in some depth [ 62 ]. In the present study, we observed that MuVs were moderately absorbed by astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates a slow internalization rate in astrocytes compared to microglia, the professional phagocytes of the CNS (Figure 1, 10). Under physiological conditions, exosome uptake regulates many functions of astrocytes, such as maintenance of BBB integrity, synaptic regulation and glutamate level modulation, providing neuroprotective services to neurons (Vasile et al, 2017; Ogaki et al, 2021). Microglia achieve excitatory neurotransmission and inflammatory response through exosome circulation (Paolicelli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, exosome uptake regulates many functions of astrocytes, such as maintenance of BBB integrity, synaptic regulation and glutamate level modulation, providing neuroprotective services to neurons (Vasile et al, 2017;Ogaki et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They play a number of significant roles in different diseases and inflammation. ECVs can affect the expression of genes and proteins, as well as the manifestations of biological activities through the regulation of intercellular communications 4 . Exosomes, as shown in Figure 1, are one of the three primary types of ECVs that cells release, along with microvesicles and apoptotic bodies 5 …”
Section: Introductionmentioning
confidence: 99%